UPAYA KEPALA SEKOLAH DALAM PEMBINAAN PROFESIONALISME GURU DI RAUDHATUL ATHFAL DIPONEGORO KECAMATAN NGAJUM KABUPATEN MALANG - Annisa Qodrun Nada; Muhammad Hanif; Eko Setiawan (Jurnal Dewantara, 2022)
This research has a background on the professionalism of teachers in educational institution. So that it is the task of the principals’s efforts to foster teachers to achieve superior educational servicer. So that the focus of this research problem is what effort can be made by school principals in fostering teacherprofesionalism ar Raudhatul Athfal Diponegoro, as well as factors that occur during the coaching process for teachers. This research uses qualitative research with a case study approach. To find out the answer to the focus of the problem, the discussion was carried out through observation, interviews, and documentation. The validity of the date is dones through triangulation. The conclusion from the result of this study, that the teacher at Raudhatul Athfal Diponegoro has not met the competence as a teacher. Efforts made by the principal are always consistent in carrying out learning supervision actions every Saturday, providing facilities for teacher self-development by involving, technical guidance, training and in the IGRA/IGTKM KKG group. In addition, there are supporting factor for school principals in their coaching effort, including: teachers have high motivation in learning and have good facilities and infastructure. While the existing inhibiting factors are the limitations and limitations of knowledge about aspect of pedagogic competence.